Korelasi Antar Karakter Pertumbuhan dan Hasil lima Genotipe Jagung Manis (Zea mays L.var saccharata) - Rahayu Eka Sari; Siti Hafsah (Universitas Teuku Umar, 2022)
ABSTRACT This study aimed to evaluate the correlation of growth and yields from five varieties of sweetcorn that is Bonanza, Secada, Royal Sweet, Sweetboy and Manise. The study was carried out in Cot Irie Village, Aceh Besar Regency, from August to November 2017 and using a non-factorial Randomized Block Design (RBD). Each variety replicated 4 times in 20 experimental plots with 20 plants in each plots so obtained 400 experimental plants. Data were analyzed by using F test and the significant differences were compared using Lowest Small Different test at probability 5 % ( LSD 0,05 ). The results of research shows differences in growth caracters, yields and correlation in observed variables. The significant positive correlation is on diameter of stem, number of corncobs, corncobs length, and diameter of corncobs.Keywords: sweetcorn, varieties, corellation, growth and yields.